Bael Tree Leaves as a Natural Adsorbent for the Removal of Zinc(II) Ions from Industrial Effluents - P. Senthil Kumar; K. Kirthika; K. Sathish Kumar (Adsorption Science & Technology)
The removal of heavy metal ions from water and wastewater has received a great deal of attention. Although adsorption methods are those most frequently used for the treatment of polluted water, such methods generally employ high-cost adsorbents such as activated carbon. The purpose of the present study was the exploration of the use of natural materials as a low-cost adsorbent in such technological applications. Thus, experiments have been conducted to test the efficiency of bael tree leaves in removing heavy metal ions, viz. Zn(II) ions, from wastewater derived from the electroplating industry. The percentage removal of Zn(II) ions was evaluated under varying experimental conditions, i.e. adsorbent dosage, initial metal ion concentration and contact time. To this effect, batch adsorption experiments were undertaken employing 2 g of 40–50 mesh bael tree leaves as an adsorbent in 100 mℓ of synthetic wastewater containing ca. 10, 20, 30, 40 and 50 mg/ℓ of Zn(II) ions. The initial pH of the synthetic wastewater was ca. 5. The experiments showed that the highest removal rate for Zn(II) ions was 88.58% under optimal conditions. Such Zn(II) ion adsorption followed reversible first-order rate kinetics. Thus, the tree leaves investigated in this study showed a good potential for the removal of Zn(II) ions from synthetic wastewater. The ultimate goal of the work described is the development of inexpensive, readily available, effective metal ion adsorbents from natural waste products as an alternative to existing commercial adsorbents.